2014
DOI: 10.1140/epjc/s10052-014-2787-5
|View full text |Cite
|
Sign up to set email alerts
|

Off-shell photon distribution amplitudes in the low-energy effective theory of QCD

Abstract: Based on the principle of Lorentz covariance the transition matrix elements from an off-shell photon state to the vacuum are decomposed into the light-cone photon distribution amplitudes (DAs), in which only two transversal DAs survive in the on-shell limit. The eight off-shell lightcone photon DAs corresponding to chiral odd and chiral even up to twist four, and the corresponding coupling constants are studied systematically in the instanton vacuum model of quantum chromodynamics (QCD). The various individual… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…In [57], In [57], Eqs. (43) and (44) are the critical masses which come into the view of the analysis of horizons for eight different cases. The cases, when M < M c1 and M = 0, the cosmological horizon appears.…”
Section: Fixed Cosmological Constantmentioning
confidence: 99%
See 1 more Smart Citation
“…In [57], In [57], Eqs. (43) and (44) are the critical masses which come into the view of the analysis of horizons for eight different cases. The cases, when M < M c1 and M = 0, the cosmological horizon appears.…”
Section: Fixed Cosmological Constantmentioning
confidence: 99%
“…Kubiznak and Mann acquired this concept and investigated the thermodynamics of the charged AdS BH in the extended phase space [26]. In this way, the investigation on thermodynamics of the many BHs has been made and many significative critical phenomena were found in [15,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][43][44][45][46][47][48][49][50][51]. Hansen et al modified the first law of thermodynamics by using the radial Einstein's equation at the Kerr BH by the surface tension [52].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was shown that a case of ensemble dependency exists for charged three-dimensional black holes which could be removed by considering the cosmological constant as a thermodynamical variable [124]. The thermodynamical critical behavior of black holes in the presence of different matter fields and gravities has been investigated in the literature [91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109].…”
Section: Introductionmentioning
confidence: 99%
“…This analogy becomes more natural in this extended phase space. Until now, these critical behaviour of a lot of black hole systems in this extended phase space are under discussion in this direction [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. It is worth to noting that, in four-dimensional Born-Infeld AdS black holes [4], the impact of the nonlinearity can bring the new phenomenon of reentrant phase transition which was observed in rotating AdS holes [19,20], while this reentrant phase transition does not occur for higher dimensional Born-Infeld AdS black holes [21].…”
Section: Introductionmentioning
confidence: 99%